2019
DOI: 10.3389/fneur.2019.01208
|View full text |Cite
|
Sign up to set email alerts
|

Primary Angiitis of the Central Nervous System Mimicking Glioblastoma: A Case Report and Literature Review

Abstract: Primary angiitis of the central nervous system (PACNS) is a rare disorder resulting in idiopathic inflammation affecting the parenchymal and leptomeningeal vessels confined to the central nervous system (CNS), of which a tumor-like mass lesion is an even rare subtype. We described a case of PACNS initially misdiagnosed as glioblastoma. The patient was a 35 year-old female with right-sided weakness and expressive dysphasia. Brain MRI showed a tumor-like lesion highly suggestive of glioblastoma, therefor surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…[27][28][29][30] Our t-PCNSV cohort had a male predominance, which was observed in previous studies. 3,6,8,25 In our cohort, the most common presentations of patients with t-PCNSV were headaches, seizures, and focal neurologic deficits, which were similar to prior studies. [6][7][8]25 In our study, even though-PCNSV had a variety of imaging patterns, we could identify several imaging features shared by many of the patients with t-PCNSV, which may help raise the possible diagnosis of this disease.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…[27][28][29][30] Our t-PCNSV cohort had a male predominance, which was observed in previous studies. 3,6,8,25 In our cohort, the most common presentations of patients with t-PCNSV were headaches, seizures, and focal neurologic deficits, which were similar to prior studies. [6][7][8]25 In our study, even though-PCNSV had a variety of imaging patterns, we could identify several imaging features shared by many of the patients with t-PCNSV, which may help raise the possible diagnosis of this disease.…”
Section: Discussionsupporting
confidence: 87%
“…Radiologic features of t-PCNSV were not well described or recognized because it is extremely rare entity. 4 To our knowledge, apart from several case reports [11][12][13][14][15][16][17][18][19][20][21][22] and review articles, [23][24][25] only a few small case series have been published in the medical literature. [6][7][8]10 Molloy et al 7 reported 8 cases of masslike PCNSV with the proved histopathology including both "Ab -related" PCNSV and "non-Ab -related" PCNSV from 2 tertiary institutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 , 12 , 13 As with our patient, white blood cell count may be normal on initial presentation in patients with brain abscesses. Jin et al 14 described a case of a young female patient who developed neurologic symptoms in the setting of a peripherally enhancing brain lesion, initially thought to represent a tumor; however, biopsy revealed this mass to be caused by a primary angiitis of the central nervous system. Similarly, a young female patient with an intracranial mass mimicking a brain tumor was instead found to have an angiitis caused by systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%